BEHRAM KI BARADARI: AN ARCHITECTURAL AND HISTORICAL STUDY OF A MUGHAL ERA MONUMENT - Shazia Bibi; Dr Rao Nadim Alam (International Journal of Contemporary Issues in Social Sciences, 2024)
This research explores the history and architecture of "Bahram Ki Braadi", a remarkable building situated in the Attock area of Pakistan. This study traces the development of this building from its construction during the Mughal era to its present state and provides an insight into its historical journey and architectural changes over time. The main objective of this study is to examine the cultural, historical and architectural aspects that characterize Bahram Ki Baradi. By examining these aspects, this study highlights the central role of the structure in the history of the Attock area and its wider significance in the context of South Asian heritage. To achieve a comprehensive understanding, this study combines a variety of research methods, including analysis of historical records, detailed architectural studies and on-site fieldwork. These approaches help uncover the layers of history embedded in the structure and provide a deeper insight into its design, purpose and cultural context. Furthermore, this research supports the preservation of Bahram Ki Bradari and recognizes that it is an important part of Pakistan's cultural heritage. This indicates the need to preserve and protect this historical building, not only for its architectural value, but also for its importance in connecting present and future generations to the local heritage. This research ultimately aims to ensure that Bahram Ki Baradi remains a well-preserved treasure of Mughal architectural talent and a symbol of Attock's heritage.